Development of a real-time recombinase-aided amplification assay for rapid and sensitive detection of Edwardsiella piscicida - Dong, Yuchen; Zhou, Dandan; Zhang, Binzhe; Xu, Xiaoying; Zhang, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
Edwardsiella piscicida, a significant intracellular pathogen, is widely distributed in aquatic environments and causes systemic infection in various species. Therefore, it’s essential to develop a rapid, uncomplicated and sensitive method for detection of E. piscicida in order to control the transmission of this pathogen effectively. The recombinase-aided amplification (RAA) assay is a newly developed, rapid detection method that has been utilized for various pathogens. In the present study, a real-time RAA (RT-RAA) assay, targeting the conserved positions of the EvpP gene, was successfully established for the detection of E. piscicida. This assay can be performed in a one-step single tube reaction at a temperature of 39°C within 20 min. The RT-RAA assay exhibited a sensitivity of 42 copies per reaction at a 95% probability, which was comparable to the sensitivity of real-time quantitative PCR (qPCR) assay. The specificity assay confirmed that the RT-RAA assay specifically targeted E. piscicida without any cross-reactivity with other important marine bacterial pathogens. Moreover, when clinical specimens were utilized, a perfect agreement of 100% was achieved between the RT-RAA and qPCR assays, resulting a kappa value of 1. These findings indicated that the established RT-RAA assay provided a viable alternative for the rapid, sensitive, and specific detection of E. piscicida.